A H2S‐Specific Ultrasensitive Fluorogenic Probe Reveals TMV‐Induced H2S Production to Limit Virus Replication. (10th May 2021) - Pang, Zhili; Ye, Haishun; Ma, Dejun; Tu, Xiaoqiang; Yi, Long; Xi, Zhen
Abstract: Understanding the role of H2 S in host defense mechanisms against RNA viruses may provide opportunities for the development of antivirals to combat viral infections. Here, we have developed a green‐emitting fluorogenic probe, which exhibits a large fluorescence response at 520 nm (>560‐fold) when treated with 100 μM H2 S for 1 h. It is highly selective for H2 S over biothiols (>400‐fold F / F 0 ) and has a detection limit of 12.9 nM. We demonstrate the application of the probe for endogenous H2 S detection in vivo for the understanding of its roles in antiviral host defense. Such virus‐induced H2 S inhibits viral replication by reducing gene expression of RNA‐dependent RNA polymerase (RdRp) and coat protein (CP). Additionally, a H2 S donor GYY4137 showed significantly antiviral activity as ribavirin, a broad‐spectrum drug against RNA viruses. Furtherly, we propose a possible molecular mechanism for the TMV‐induced H2 S biogenesis. This work provides a proof‐of‐principle in support of further studies identifying endogenous H2 S and its donors as potential antivirals toward RNA viruses. Abstract : H2 S biogenesis promoted by TMV invasion is visualized by a highly sensitive and selective fluorogenic probe, highlighting H2 S as an endogenous defense against RNA viruses.